Inventory model for deteriorating items with time and reliability dependent demand and partial backorder. (2017) - Mahapatra, G.S.; Adak, Sudip; Mandal, T.K.; Pal, Shilpi
The objective of this paper is to show how providing high-quality reliable products and balancing of the stock availability to maintain customer satisfaction can be the key factor in governing the inventory management of a company which in turn can increase its market share, productivity, and profitability. So, an economic order quantity (EOQ) model is developed to analyse the effect of reliability and time-based demand rate on inventory management system. The effect of constant deterioration and shortages are permitted with partial backlogging. The core objective of a good inventory management system is to provide the best possible customer service within the restraint of the lowest practical inventory costs. Thus, a minimisation of the total inventory cost has been tried to achieve with optimisation of inventory. To support our study, we have illustrated it with a numerical example and finally, sensitivity analysis is carried out to find the effect of the parameters on the optimal solution.